Implementasi Kurikulum Merdeka dalam Meningkatkan Keaktifan dan Mutu Belajar Siswa di SMP Madya Utama Medan - Gulo, Nurhayati; Simanjuntak, Hotmaida; Pasaribu, Kondios Meidarlin (YASIN, 2025)
This research is motivated by the many applications of the independent curriculum that are still not maximal in various schools, especially classroom learning that is still the same as the previous curriculum. The purpose of this study is to analyze the implementation of the Independent Curriculum in improving the activeness and quality of student learning at SMP Madya Utama as one of the best examples of schools in the implementation of the independent curriculum. This study uses a qualitative method with a descriptive approach. Data was obtained through observations, interviews, and documentation from the principal, 2 teachers and 6 students in the school environment. The research analysis used was B Miles and Huberman with the validity of data through data sources. The results of the study show that the implementation of the Independent Curriculum in SMP Madya Utama has a positive impact on student activity in the learning process, especially through project-based learning and collaborative activities. In addition, the quality of student learning has also improved, which is shown by the improvement of critical thinking skills, creativity, and responsibility and independence in learning. This is because at SMP Madya Utama all teachers are required to take part in various independent curriculum trainings both held by the school every semester and by teacher groups every year. Although there are still obstacles in implementation, especially the maximum use of technology, the school strives to provide solutions for teachers, especially those who have entered old age, to understand the technology of educational applications and websites well from various activities. The implications of this research are field-based, and there are still opportunities to strengthen each other's data, especially using other research methods.